"Maybe you don’t know what answers I want": unresolved alliance ruptures preceding dropout in short-term psychoanalytic psychotherapy with depressed adolescents - Manuela Jose Difronzo; Lisa Thackeray; Sally O'Keeffe; Ana Calderon; Nick Midgley (Research in Psychotherapy)
The therapeutic alliance is a predictor of therapy outcome across treatments with adolescents, with ruptures and unresolved ruptures in the alliance being associated with treatment dropout. This study investigated the psychotherapeutic process in short-term psychoanalytic psychotherapy (STPP) with five adolescents with moderate/severe depression who had dropped out of STPP in a large randomized controlled trial and reported dissatisfaction with treatment. In each case, sessions were rated as featuring unresolved ruptures with the therapist. This study aimed to explore the processes characterising ruptures preceding dropout using the Adolescent Psychotherapy Q-set (APQ). Data were analysed using descriptive statistics of the APQ coding; a qualitative reading of the transcripts and clinical vignettes was used to illustrate how the APQ findings manifested in practice. Results revealed a weak alliance preceding the adolescent dropping out of therapy, with a mismatch between self-reliant and disengaged adolescents presenting with strong negative affects and therapists seeking to maintain an active exploration of the adolescents’ difficulties. Research and clinical implications are discussed.